Aboriginal earth mounds of the Calperum Floodplain (Murray Darling Basin, South Australia): New radiocarbon dates, sediment analyses and syntheses, and implications for behavioural change. (August 2022) - Jones, Robert; Roberts, Amy; Westell, Craig; Moffat, Ian; Jacobsen, Geraldine; Rudd, Rachel
This paper presents the results of an archaeological investigation into anthropogenic earth (oven) mounds located on the Murray River floodplain at Calperum Station in the Renmark region of South Australia. Six mounds were excavated and their contents examined. Sediment analyses were also conducted to assess magnetic susceptibility, grain size and loss on ignition. Radiocarbon age estimates were obtained on shell and charcoal. Mound contents primarily included anthropogenically burnt clay (heat retainers), charcoal, fragments of mussel shell as well as very minor quantities of other faunal material and stone artefacts (which were consistent with previous lithic assessments for the region). The radiocarbon age determinations from 15 samples indicate that mounds were formed by Aboriginal people on the Calperum floodplain from at least 3981–3723 cal BP and utilised up to the time of European invasion. The very minimal amount of faunal remains (other than mussel shell), artefacts and a general lack of other material evidence apart from clay heat retainers, confirms that these features were single purpose and not used as living areas. Sediment analyses and radiocarbon dates indicate a high degree of homogeneity within mounds but provide insights into an economic transition on the Calperum floodplain, at around 4000 cal BP involving a food-production procurement strategy based on heat retainer technology and the exploitation of emergent macrophytes.